Correlation between the Activity of Aldehyde Dehydrogenase and Oxidative Stress Markers in the Saliva of Diabetic Patients - Younus, Hina; Ahmad, Sumbul; Alam, Md. F. (Protein and Peptide Letters, 2020)
Background: Reactive aldehydes are involved in diseases associated with oxidative stress, including diabetes. Human salivary aldehyde dehydrogenase (hsALDH) presumably protects us from many toxic ingredient/contaminant aldehydes present in food. Objective: This study aimed to probe the activity of hsALDH in patients with diabetes and than to correlate it with various oxidative stress markers in the saliva. Methods: The saliva samples were collected from total 161 diabetic patients from Rajiv Gandhi Centre for Diabetes, Jawaharlal Nehru Medical College (JNMC), AMU, Aligarh, (India). HsALDH activity and markers of oxidative stress [8-hydroxydeoxyguanosine (8-OHDG), malondialdehyde (MDA) and advanced glycation end products (AGEs)] were measured in the saliva samples. Results: Patients with early stage of diabetes had higher activity of hsALDH when compared with the control group. As the history of diabetes increases, the activity of the enzyme decreases and also higher oxidative stress markers (8-OHDG, MDA and AGEs) are detected in the saliva samples. Negative significant correlation between hsALDH activity and oxidative stress markers were observed (p <0.0001). Conclusion: The activity of hsALDH increases in early stages of diabetes most probably to counter the increased oxidative stress associated with diabetes. However, in later stages of diabetes, the activity of the enzyme decreases, possibly due to its inactivation resulting from glycation.
Keywords: human salivary aldehyde dehydrogenase